Dark Soliton Array for Communication Security - I.S. Amiri; A. Afroozeh; I.N. Nawi; M.A. Jalil; A. Mohamad; J. Ali; P.P. Yupapin (My University, 2011)
A system of dark soliton array (DSA) for secured optical communication using the multiplexed dark soliton pulses is presented. Different wavelength of input soliton pulses with relevant parameters are fed into the rings system while the radii of the rings are 7 μm, 5 μm and Rd = 50 μm. Result shows that the free spectrum range of dark soliton input with the center wavelength of 1503 nm is 0.073 nm. DSA can be obtained using a series of micro ring resonators with input optical solitons of different wavelength, range from λ = 1513 nm to λ = 1517 nm. The DSA can be tuned and amplified used for many application in optical communication such as security purposes. In transmission link, the long distance link of the multi variable network can be performed using DSA.
Keywords: Advanced Fiber Laser Technologies